Temperature Estimates of Lower Miocene (Burdigalian) Coastal Water of Southern India Using a Revised Otolith "Clumped" Isotope Paleothermometer. (7th December 2021) - Prasanna, K.; Ghosh, Prosenjit; Eagle, Robert A.; Tripati, Aradhna; Kapur, Vivesh V.; Feeney, Richard F.; Fosu, Benjamin R.; Mishra, Divya
Abstract: Carbonate clumped isotope thermometry is based on the ordering of 13 C and 18 O in the carbonate lattice and is based on the relative abundance of 13 C 18 O 16 O in CO2 produced through acid digestion of carbonate minerals. The major advantage of this technique is its non‐dependency on the δ 18 O value of water from which the carbonate precipitated. Ghosh et al. (2007, https://doi.org/10.1016/j.gca.2007.03.015 ) previously published calibration data for fish otoliths referenced to heated gases and used the Gonfiantini 17 O parameter set in their data evaluation. Herein, we present a new clumped isotope (Δ47 ) calibration for aragonitic fish otoliths in the absolute reference frame using the International Union of Pure and Applied Chemistry 17 O correction. Our revised calibration equation for otolith is: Δ 47 CDES = 0.0364 ± 0.005 × ( 10 6 ) T 2 + 0.2619 ± 0.0657 ( R 2 = 0.9, p − value < 0.001 ) . To test the accuracy of this calibration, we apply it to otoliths of modern Lutjanus lutjanus from the Bay of Bengal. The estimated average temperature (22.3°C ± 4.2°C) for the Bay of Bengal and δ 18 OV‐SMOW composition of waters of −1.7‰ (±0.5) are consistent with the onsite observations. We also apply the new calibration to well‐preserved otoliths of "genus Ambassidarum" sp. and "genus Gobiidarum" sp. from lower Miocene (Burdigalian) sediments of the Quilon Formation, India to quantify coastal water conditions. Estimated average environmental water temperatures in their habitats were 12.9°C ± 1.7°C, and the average δ 18 OV‐SMOW of ambient waters calculated yielded a value between −3.5‰ and −2.6‰ (V‐SMOW) (mean: −2.9‰ ± 0.4) and −4.4‰, respectively. These results indicate δ 18 O values reflect the kinetic effects impacting the δ 18 O of fish otoliths independently of Δ47, although we cannot fully preclude diagenesis. Key Points: A revised clumped isotope calibration equation for otoliths was established based on the International Union of Pure and Applied Chemistry parameter set The new calibration equation is validated by quantifying the environmental water δ 18 O of modern waters New calibration equation allows for the reconstruction of lower Miocene coastal conditions in southwest India utilizing fossil otoliths